Assessing Motorcycle Safety Helmet Standards Compliance - Hamzah, A.; Helmy Syamza, M.T.S.; Ahmad, M.A.; Ariffin, A.H.; Solah, M.S.; Paiman, N.F. (Journal of the Society of Automotive Engineers Malaysia, 2021)
This study attempts to analyse new helmet performance which was certified to MS1:1996 standards (impact energy attenuation and penetration resistance) with respect to a newly established standard MS1:2011 which has a strong resemblance to the United Nations Regulation No 22 (UNR22). Few helmet models were randomly purchased and tests were performed in an established technical laboratory. The result indicated that one of five popular models was able to meet the requirements of the new standards. The rest of the helmet samples were only managed to pass partially, for example they performed well in the frontal impact test but performed poorly in the lateral impact. Few helmets failed to meet the minimum impact speed requirements. In brief, the new standards are more comprehensive and have more demanding requirements for existing product range to comply with and some changes to the existing helmet design may be necessary and it is achievable.